KELAYAKAN MEDIA PEMBELAJARAN BIOLOGI DALAM BENTUK SPESIMEN PADA MATERI ORGAN TUMBUHAN DI SMPN 5 RAMBAH HILIR - Nurul Afifah; Vergi Putri Windayat; Ria Karno (Universitas Khairun, 2017)
The purpose of the research to determine the properness of biology learning media in specimen form on plant organ material in state high school junior 5 Rambah Hilir. This Research was done from June to August 2016. The type of the research was the development of research (Research and development) which developed by Dick and Carey and have been modified. The data collection was done by using the questionnaire and analyzed descriptively. The results showed that the learning media specimen material plants organ at grade VII SMPN 5 Rambah Hilir based on the validation of subject matter experts (81.24%) by the categorized as very proper, validation media expert (72,91%) with feasible category, individual testing (95,7%) with the very feasible category, small group trial (94%) categorized as very feasible and field trials (95,78%) categorized as very feasible.Key Words: Specimen, Plants Organ, Learning Media